Clinical pharmacist recommendations in daily interdisciplinary ward rounds at a psychiatric hospital: a retrospective pre-post study on drug-related problems focused in somatic comorbidities - Stuhec, Matej; Gazdag, Anteja Gorjan; Cuk, Zala; Oravecz, Robert; Batinic, Borjanka (Frontiers in Psychiatry, 2024)
ObjectiveOne potential strategy to address inadequate screening for somatic comorbidities among patients with mental disorders is to integrate a clinical pharmacist into the inpatient team for daily interdisciplinary ward rounds. This approach remains under-researched in psychiatric hospitals. This study aimed to evaluate the impact of a clinical pharmacist on drug-related problems (DRPs) during daily ward rounds within an interdisciplinary team in a psychiatric hospital.MethodsA retrospective observational pre-post study was conducted at the Ormož Psychiatric Hospital in Slovenia, including patients treated between 2019 and 2020, during which clinical pharmacists offered recommendations during daily ward rounds. The primary outcomes assessed the difference in the total number of DRPs observed at the time of hospital discharge compared to previous stage, as well as the recommendations and their continuation rate after three months. The secondary outcomes evaluated adherence to treatment guidelines.ResultsThe study included 186 patients (mean age: 58.1 years, SD=17.0). During ward rounds, 280 recommendations related to DRPs were conducted (1.5 recommendations per patient). Regarding the nature of DRPs, 154 (55.0%) were identified as expressed DRPs, while 127 (45.0%) were deemed potential DRPs. Following pharmacist recommendations, 133 (86.4%) of the expressed DRPs were successfully resolved. The majority of DRPs pertained to treatment effectiveness (N=179, 63.9%), followed by unnecessary treatments (N=86, 30.7%) and patient safety (N=15, 5.4%). Initially, the acceptance rate of recommendations was 88.9% (N=249) at discharge, declining to 63.2% (N=177) three months after discharge. The acceptance rate for somatic conditions at discharge was 87.8% (N=122), declining to 59.0% (N=82) three months after discharge. Adherence to treatment guidelines for somatic comorbidities increased (p < 0.05).ConclusionsThe results indicate that this approach led to fewer DRPs, a high rate of acceptance, and better adherence to treatment guidelines. This is the first retrospective pre-post study in the European Union to include this collaboration in daily rounds at psychiatric hospitals, focusing on somatic comorbidities. However, the study also has significant limitations, such as its non-randomized design and short monitoring period, which should be addressed in future research.